2015
DOI: 10.1177/2158244015587558
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Predictors of Relationship Conflict Styles as Mediated by Emotional Intelligence

Abstract: This study investigated the influence of age, gender, and emotional intelligence (EI) on conflict management styles among dating age adults in Botswana. A mixed survey and quasi-experimental design was used to assess the relationship between age and gender and the mediating influence of EI on participants' preferred conflict management strategies (avoidance, competition, compromise, accommodation, and collaboration) in response to violent and nonviolent relationship conflict. One hundred fifty-two participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
3
1
1
Order By: Relevance
“…The results of this study suggest a significant relationship between emotional intelligence and conflict management styles, as high EI was associated with the use of integrating style, compromising style and obliging style, while low EI was associated with the use of dominating style and avoiding style. This matches the results of various studies (Başoğul & Özgür, 2016;Chan et al, 2014;Hopkins & Yonker, 2015;Monteiro & Balogun, 2015;Schlaerth et al, 2013;Sehrawat & Sharma, 2014). The study of the Pandey et al (2015) contradicted the result of this present study, as it revealed that high EI was associated with the use of avoiding style.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study suggest a significant relationship between emotional intelligence and conflict management styles, as high EI was associated with the use of integrating style, compromising style and obliging style, while low EI was associated with the use of dominating style and avoiding style. This matches the results of various studies (Başoğul & Özgür, 2016;Chan et al, 2014;Hopkins & Yonker, 2015;Monteiro & Balogun, 2015;Schlaerth et al, 2013;Sehrawat & Sharma, 2014). The study of the Pandey et al (2015) contradicted the result of this present study, as it revealed that high EI was associated with the use of avoiding style.…”
Section: Discussionsupporting
confidence: 91%
“…The study also revealed that age was not significantly correlated with emotional intelligence (Schlaerth, Ensari, & Christian, ). These results were not congruent with the results of Pandey, Sajjanapu, and Sangwan () and Monteiro and Balogun ().…”
Section: Introductioncontrasting
confidence: 81%
“…It turns out that people with high emotional intelligence are more positively perceived by others, more popular, and their relationships with other people are more intense and characterized by greater durability and higher quality (Alonso-Ferres, Valor-Segura, Expósito, 2019; Antonysamy, Asgarali Patel, Velayudhan, 2020; Gündüz, 2019;Negi, Balda, 2019;O'Connor, Izadikhah, Abedini, Jackson, 2018;Szczygieł, Weber, 2017;Wollny, Jacobs, Pabel, 2020). They also cope better with conflict and interpersonal problems (Alonso-Ferres, Valor-Segura, Expósito, 2019; Monteiro, Balogun, 2015;Vashisht, Singh, Sharma, 2018). Emotionally intelligent people are more likely to engage in altruistic and cooperative behaviors (Barragan Martin et al, 2021;Enwereuzor, Ugwu, 2021;Huang, Shi, Liu, 2018;Mandal, Mehera, 2017).…”
Section: Emotional Intelligence and Its Role In Human Functioningmentioning
confidence: 99%
“…Moreover, Lopes et al (2004) noted that people with greater EI ability tend to inhibit behaviours that are negative or destructive. Likewise, the role of EI in the positive conflict resolution as a form of marital quality among married couples was found based on EI self-report mixed model (Batool & Khalid, 2012;Monteiro & Balogun, 2015;O'Connor et al, 2018).…”
Section: Emotional Intelligence and Conflict-facing Responses: Links mentioning
confidence: 99%